The Design of a Homogeneous Magnetic Field Generator for Applications in Membrane Making - Gayatri, Ida Ayu Putu Inten; Rupiasih, Ni Nyoman; Sumadiyasa, Made (BULETIN FISIKA; Vol 20 No 1 (2019): BULETIN FISIKA, 2019)
It has been designed a homogeneous magnetic field (B) generation system in a particular room. This is important to conduct research related to the effects of magnetic field exposure on chemical reactions, especially in the process of making membranes. The development was carried out using four Helmholtz coils which radius (R) of 15 cm and number of turn (N) of 130 turns, that connected in parallel and coaxial. The both coils were fixed at the same distance as the radius of the coil that intended to get a homogeneous magnetic field between the both coils. The design has been tested by measuring a magnetic field generated as function of a current (I) given. The results show that, for x is the distance from the midpoint of the both coils to a certain distance, the homogeneous magnetic field obtained in the region of -7 cm < x <+7 cm, the area between the both coils. The magnitude of the homogeneous magnetic field produced depends on the electric current given.